1980
DOI: 10.1289/ehp.803459
|View full text |Cite
|
Sign up to set email alerts
|

Elemental modifications and polycyclic aromatic hydrocarbon metabolism in human fibroblasts

Abstract: Mineral fibers and particulates represent one of the best documented, economically important, and ubiquitously occurring categories of human carcinogens. Yet, while a wealth of information exists concerning the mechanism of action of physical, chemical, and viral carcinogens, virtually nothing is known relative to the mechanism of action of this economically important class of carcinogenic compounds known as mineral fibers and particulates. While the length and diameter of various forms of asbestos have been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1983
1983
1985
1985

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Thus, consistent with earlier results using NIEHS intermediate chrysotile (34,35), the simultaneous addition of NIEHS short chrysotile and B(a)P did not enhance, in a dose-dependent manner, the metabolism and subsequent DNA binding of the hydrocarbon in human fibroblasts. However, when the B(a)P-DNA adducts formed in the presence of 1 mg/mL NIEHS short chrysotile were compared by HPLC analysis with those generated in the absence of the fiber, the relative amounts of the various enantiomeric B(a)P-deoxyribonucleoside adducts appeared to be altered.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, consistent with earlier results using NIEHS intermediate chrysotile (34,35), the simultaneous addition of NIEHS short chrysotile and B(a)P did not enhance, in a dose-dependent manner, the metabolism and subsequent DNA binding of the hydrocarbon in human fibroblasts. However, when the B(a)P-DNA adducts formed in the presence of 1 mg/mL NIEHS short chrysotile were compared by HPLC analysis with those generated in the absence of the fiber, the relative amounts of the various enantiomeric B(a)P-deoxyribonucleoside adducts appeared to be altered.…”
Section: Discussionsupporting
confidence: 92%
“…This latter observation is of interest, since DiPaolo et al (36) have reported a synergism between asbestos fibers and BP with respect to SHE cell transformation. The simultaneous addition of NIEHS chrysotile and BP to normal human fibroblasts did not result in either increased BP metabolism (41,43,44), altered BP-metabolite profiles, cytotoxicity (41,43), BP-DNA binding levels (43,44), or in substantially altered BP-deoxyribonucleoside adduct profiles (44). These studies and others discussed by Mossman (45), may indicate that asbestos fibers act as the level of a cocarcinogen or promoter with respect to their oncogenic effects.…”
mentioning
confidence: 57%
“…Normal human fibroblasts (human foreskin, line 149) were cultured at the 16th or 17th passage in Eagle's minimum essential medium, supplemented with 10% fetal bovine serum (GIBCO) (21). Confluent fibroblast monolayers were harvested by trypsinization (0.01% trypsin in 0.01% EDTA) and dispersed in growth medium to achieve a single-cell suspension.…”
Section: Fibroblast Toxicity Assaymentioning
confidence: 99%